HOMOLOGATION TESTS OF SINGLE-STAGE R02 REDUCER - Katarzyna RADZIEWICZ; Krzysztof GARBALA; Michał CEGŁOWSKI (Scientific Journal of Silesian University of Technology. Series Transport, 2018)
This article presents the results of homologation tests of an LPG reducer. Due to the material requirements of the LPG reducer in this case, the R02 reducer, designed by the joint-stock company AC Spółka Akcyjna, is used. Test procedures, which must be carried out, are also presented and generally explained with specified conditions for conducting the processes. The advantages of using the R02 are also presented. The properties of aluminium alloy 226, which is the body of the reducer, are characterized and are divided into four groups: technological features/qualitative indications, physical properties, mechanical features and chemical composition. The whole article is summarized with appropriate conclusions.